An Update on Ethylenediaminetetraacetic Acid for Optimal Endodontic Outcomes: A Narrative Review - Gaeta, C.; Hämäläinen, H.; Malvicini, G.; Gliga, A.; Vakili, M.; Grandini, S. (Journal of Osseointegration, 2025)
Aims Ethylenediaminetetraacetic acid (EDTA) is a chelating agent primarily used in the final rinse to remove the smear layer formed during mechanical root canal preparation. This study aims to review the latest scientific insights on EDTA, evaluate its necessity in irrigation protocols, compare its effectiveness with alternative options, and eventually provide a concise, practical conclusion on the necessity of EDTA in a successful irrigation protocol. Materials and Methods and Results Reviewing numerous articles, this article suggests that EDTA can effectively remove the smear layer, enhancing canal cleanliness, it has notable antimicrobial properties, and also effectively increasing dentine permeability. While EDTA is a legitimate and accepted clinical practice as final rinsing in root canal therapy, current evidence suggests that it may not be the unique optimum choice in all cases. Alternatives such as citric acid, which is less aggressive to dentinal tubules, and carbohydrate-derived fulvic acid, which demonstrates superior smear layer removal, show promise as better options. Conclusions Further studies are needed to clarify the comparative efficacy and safety of these alternatives, as well as to determine whether EDTA remains the most appropriate choice in clinical practice.